Spatial variability of soil macronutrients at farm-scale in irrigated plains under rice-wheat cropping system - BUTTAR, TEJBIR SINGH; SHARMA, VIKAS; WANI, OWAIS A.; ARYA, VIVAK M.; MANHAS, SWEETA; THAKUR, AJAY (Journal of Soil and Water Conservation, 2026)
Soil characteristics vary drastically even over short distances. For sustainable crop production, farm- level precision nutrient management necessitates an understanding of the spatial variability of soil nutrients. However, small-scale nutrient data are insufficient for effective management on farms. Grid- based sampling offers a viable approach for large-scale assessment to delineate nutrient-deficient zones. A study was conducted at Chakroi Farm, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu (SKUAST-J), to evaluate the spatial variability of soil macronutrients at the farm scale. The highest variability was recorded for sulphate-S (SO4-S) in both surface (0-15 cm; 70.27%) and sub-surface (15-30 cm; 79.94%) layers, whilst the least was recorded for available-N (18.45%) and available- P (19.47%). In the surface layer, the spherical model was the best fit for available N, whereas the exponential model fit all other macronutrients. In the sub-surface layer, the Gaussian model was the best fit for available P, K, and SO4-S, while the exponential model best described available N. Approximately 50% of the farm area had medium levels of available-N, with the remainder in the low range. Over 40% of the area had available-P between 11–15 mg kg-1. Surface soil available K predominantly ranged from 50–75 mg kg-1, while sub-surface K was lower in the western region (25–50 mg kg-1), increasing toward the southeast. Most SO4-S values exceeded the critical threshold of 10 mg kg-